Impact of Migration and Acculturation on Prevalence of Type 2 Diabetes and Related Eye Complications in Indians Living in a Newly Urbanised Society - Zheng, Yingfeng; Lamoureux, Ecosse L.; Ikram, M. Kamran; Mitchell, Paul; Wang, Jie Jin; Younan, Christine; Anuar, Ainur Rahman; Tai, E-Shyong; Wong, Tien Y. (Public Library of Science, 2012)
Background: Health of migrants is a major public health challenge faced by governments and policy makers. Asian Indians are among the fastest growing migration groups across Asia and the world, but the impact of migration and acculturation on diabetes and diabetes-related eye complications among Indians living in urban Asia remains unclear. Methodologies/Principal Findings: We evaluated the influence of migration and acculturation (i.e., migration status and length of residence) on the prevalence of type-2 diabetes mellitus (T2DM) and diabetes-related eye complications (diabetic retinopathy (DR) and cataract), among first-generation (defined as participant born in India with both parents born in India, n = 781) and second-generation (participants born in Singapore with both parents born in India, n = 1,112) Indian immigrants from a population-based study of Adult Indians in Singapore. Diabetes was defined as HbA1c≥6.5%, use of diabetic medication or a physician diagnosis of diabetes. Retinal and lens photographs were graded for the presence of DR and cataract. Compared to first generation immigrants, second generation immigrants had a higher age- and gender-standardized prevalence of T2DM (34.4% versus 29.0%, p<0.001), and, in those with T2DM, higher age- and gender-standardized prevalence of DR (31.7% versus 24.8%, p<0.001), nuclear cataract (13.6% versus 11.6%, p<0.001), and posterior sub-capsular cataract (6.4% versus 4.6%, p<0.001). Among first generation migrants, longer length of residence was associated with significantly younger age of diagnosis of diabetes and greater likelihood of having T2DM and diabetes-related eye complications. Conclusion: Second generation immigrant Indians and longer length of residence are associated with higher prevalence of diabetes and diabetes-related complications (i.e., DR and cataract) among migrant Indians living in Singapore. These data highlight potential worldwide impacts of migration patterns on the risk and burden of diabetes. © 2012 Zheng et al.